Human Capital, Social Capital, And Innovation Capability In Performance Of Village-Owned Enterprises - Yesi Mutia Basri; Hariadi Yasni; Al Azhar-A; Rheny Afriana Hanif; Rezi Abdurrahman (Jurnal ASET (Akuntansi Riset), 2021)
This study aims to analyze the effect of human capital and social capital on the performance of Village-owned Enterprises which is mediated by innovation capability. The population in this study is Village-owned Enterprises located in Kampar Regency. Respondents in this study were the director of BUMdes. as many as 228 Village-owned Enterprises. The data collection technique is by sending a questionnaire in the form of an internet questionnaire designed using Google Forms. A total of 120 BUMDes Directors participated in this research. The results of data analysis with PLS show that the results of the study indicate that human capital does not affect the performance of Village-owned Enterprises. Social capital affects the performance of Village-owned Enterprises. Social capital and human capital have also been shown to affect the ability to innovate. Social capital has also been shown to affect humans and innovation capability affects performance. The ability of innovation can also partially mediate the relationship of social capital with the performance of Village-owned Enterprises and fully mediate the effect of special capital on the performance of Village-owned Enterprises. However, human capital is not a mediating variable for the effect of social capital on Village-owned Enterprises performance. This research has a contribution to improving the performance of Village-owned Enterprises.